Analysis of the Impact of Fast Fashion and Thrifting on the Local Textile Industry and the Environment: A Consumer Market Segmentation Perspective in Indonesia - Rizqiatul Camelia; Abdur Rohman (Penerbit Hellow Pustaka, 2025)
The fast fashion and thrifting phenomena in Indonesia have triggered significant changes in the dynamics of the local textile industry and aspects of environmental sustainability. This study aims to analyze the impact of both trends from the perspective of consumer market segmentation. The method used is a descriptive qualitative approach with library research techniques on various relevant scientific sources. The results of the study indicate that the fast fashion trend accelerates the consumption cycle through low-cost mass production, while thrifting encourages consumer behavior and reflects early awareness of sustainable fashion. These two trends create serious challenges for local textile MSMEs in terms of price competitiveness, brand image, and adaptation to changes in consumer preferences. In addition, illegal imports of used clothing also have negative impacts on the environment and public health. This study suggests the need for stricter policies, consumer education, and strengthening the narrative of national identity in order to build a competitive and sustainable local textile industry.